Differential Regulation of Bk Channels by Fragile X Mental Retardation Protein - Rojas-Montecinos, P (Rockefeller University Press, 2020)
Fragile X mental retardation protein (FMRP) is an RNA-binding protein prominently expressed in neurons. Missense mutations or complete loss of FMRP can potentially lead to fragile X syndrome, a common form of inherited intellectual disability. In addition to RNA regulation, FMRP was also proposed to modulate neuronal function by direct interaction with the large conductance Ca2+- and voltage-activated potassium channel (BK) β4 regulatory subunits (BKβ4). However, the molecular mechanisms underlying FMRP regulation of BK channels were not studied in detail. We have used electrophysiology and super-resolution stochastic optical reconstruction microscopy (STORM) to characterize the effects of FMRP on pore-forming BKα subunits, as well as the association with regulatory subunits BKβ4. Our data indicate that, in the absence of coexpressed β4, FMRP alters the steady-state properties of BKα channels by decreasing channel activation and deactivation rates. Analysis using the Horrigan-Aldrich model revealed alterations in the parameters associated with channel opening (L0) and voltage sensor activation (J0). Interestingly, FMRP also altered the biophysical properties of BKαβ4 channels favoring channel opening, although not as dramatically as BKα. STORM experiments revealed clustered multi-protein complexes, consistent with FMRP interacting not only to BKαβ4 but also to BKα. Lastly, we found that a partial loss-of-function mutation in FMRP (R138Q) counteracts many of its functional effects on BKα and BKαβ4 channels. In summary, our data show that FMRP modulates the function of both BKα and BKαβ4 channels. © 2020 Kshatri et al. This article is distributed under the terms of an Attribution-Noncommercial-Share Alike-No Mirror Sites license for the first six months after the publication date (see http://www.rupress.org/terms/). After six months it is available under a Creative Commons License (Attribution-Noncommercial-Share Alike 4.0 International license, as described at https://creativecommons.org/licenses/by-nc-sa/4.0/).